Sentinel node biopsy after primary systemic therapy in node positive breast cancer patients: Time trend, imaging staging power and nodal downstaging according to molecular subtype. Issue 6 (June 2019) - Di Micco, Rosa; Zuber, Veronica; Fiacco, Enrico; Carriero, Federica; Gattuso, M. Ilaria; Nazzaro, Ludovica; Panizza, Pietro; Gianolli, Luigi; Canevari, Carla; Di Muzio, Nadia; Pasetti, Marcella; Sassi, Isabella; et al.
Abstract: Background: The management of axilla after Primary Systemic Therapy (PST) for breast cancer is a highly debated field. Despite the proven axillary downstaging occurring after PST, there is still some degree of reluctance in applying sentinel node biopsy (SNB) in the neoadjuvant setting. Patients and methods: We performed a retrospective analysis on 181 PST patients with axillary positive nodes at presentation treated between 2005 and 2017 at San Raffaele Hospital in Milan. The aim was to observe the application time trend of SNB, to determine the imaging staging power and the axillary downstaging according to molecular subtypes. Results: Median follow-up after surgery was 32.5(IQR: 12–59) months. After PST, 119 (65.7%) patients had no clinically palpable nodes, 72 (39.7%) converted to N0 on final imaging and 34 (18.8%) underwent SNB with an increasing application trend. Axillary-US showed the highest accuracy (69.3%) in re-staging axilla after PST. Staging power of preoperative testing varied with tumour biology: Positive Predictive Value was higher in Luminal A (80% for clinical examination and 100% for axillary-US) and Luminal B (72% and 70.5%) tumours, whilst Negative Predictive Value was higher in HER2 positive (100% and 93.3%), and triple negative (71.4% and 93.3%) tumours. Ninety five (52.5%) patients experienced axillary downstaging after PST, by molecular subtype 15% (3/20) in Luminal A, 46.4% (45/97) in Luminal B, 90.9% (20/22) in HER2+ and 70.3% (26/37) in triple negative breast tumours. Conclusion: SNB application after PST for breast cancer in node positive patients at presentation is increasing. Pre-operative axillary imaging and tumour biology help identify patients who might be candidates for SNB as a single staging procedure.